(untitled) (Research, Society and Development, 2020)
Basil (Ocimum basilicum L.) is a sub-shrub native to Tropical Asia and introduced in Brazil by the Italian colony. It is an annual crop plant, culinary use in various regions of the world. The present work aimed to evaluate the influence of carnauba (Copernicia prunifera) bagana as substrate on the vegetative propagation of basil. The experiment was conducted at the Federal University of Maranhão in Chapadinha-MA. A completely randomized design with 6 treatments of carnauba bagana substrate (BC) in the following proportions: 0%, 20%, 40%, 60%, 80% and 100% plus soil, with 4 replications, 2 cuttings per tube totaling 48 piles. At 45 days, the seedlings were evaluated in the laboratory for the following characteristics: Plant height, number of leaves, number of shoots, stem diameter, root length and volume, leaf area, fresh mass of shoot and root system, mass shoot and root system drought and Dickson quality index. Data were subjected to analysis of variance and explored by regression using the Infostat® software. The use of carnauba bagana substrate had a significant effect on the variables under study, except for the number of shoots and plant height. The proportions of carnaúba bagana that provided greater seedling development were from 40% to 80% to BC plus soil.